Indonesia Penerapan Kecerdasan Buatan dalam Pembelajaran Sains - Amir, Nur Insani; Arafah Nurfadillah; Marshanda D. Abd. Karim (Education and Talent Development Center Indonesia, 2025)
Artificial intelligence (AI)-based tools and software are very easy to find and some of them can be accessed for free. There are various types of AI-based tools and software that can be used to increase student interest and learning experience. This activity aims to increase students' knowledge about the use of tools and software to support the science learning process. This activity is descriptive and experimental, starting from the process of delivering material, simulating the use of tools and software, and discussions. The number of participants was 29 students and 3 science teachers in the science classrooms and laboratories of SMAS Immim Putra Makassar.